2021
DOI: 10.3389/fcell.2021.629893
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-15a Carried by Mesenchymal Stem Cell-Derived Extracellular Vesicles Inhibits the Immune Evasion of Colorectal Cancer Cells by Regulating the KDM4B/HOXC4/PD-L1 Axis

Abstract: The relevance of microRNA-15a (miR-15a) to autoimmunity has been reported. Herein, we intended to probe the potential roles of miR-15a shuttled by adipose-derived mesenchymal stem cells (adMSCs)-derived extracellular vesicles (Evs) in colorectal cancer (CRC). Initially, CRC cells were treated with interferon gamma (IFN-γ) to screen out differentially expressed genes by transcriptome sequencing. Following a 24-h co-culture with 20 μM adMSCs-derived Evs, CRC cell viability, migration, invasion, and apoptosis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 33 publications
(34 reference statements)
1
27
0
Order By: Relevance
“…The present study demonstrated a signi cant positive correlation between KDM4B and CTLA4 and SIGLEC15 respectively, which may inhibit the immune response of UCEC patients through excessive immunosuppression leading to immunologic escape of malignant tumor cells resulting in poor prognosis of malignant tumor. Mesenchymal stem cell-derived extracellular vesicles overexpressing miR-15a limit immunologic escape in colorectal cancer (CRC) via the KDM4B/Hoxc4/PD-L1 axis, and this study con rms our ndings (12). In addition, immune checkpoint blockade using anti-PD1/PD-L1/CTLA4 antibodies improved the prognosis of patients with refractory solid tumors.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The present study demonstrated a signi cant positive correlation between KDM4B and CTLA4 and SIGLEC15 respectively, which may inhibit the immune response of UCEC patients through excessive immunosuppression leading to immunologic escape of malignant tumor cells resulting in poor prognosis of malignant tumor. Mesenchymal stem cell-derived extracellular vesicles overexpressing miR-15a limit immunologic escape in colorectal cancer (CRC) via the KDM4B/Hoxc4/PD-L1 axis, and this study con rms our ndings (12). In addition, immune checkpoint blockade using anti-PD1/PD-L1/CTLA4 antibodies improved the prognosis of patients with refractory solid tumors.…”
Section: Discussionsupporting
confidence: 83%
“…Recent studies have suggested that KDM4B facilitates in the regulation of PI3K(8), TGF-β, Notch, and Wnt/βcatenin pathways (9) during malignant transformation of cancer and researches also indicated that KDM4B was a potential biomarker for targeted therapy of these cancers (10,11). Encouragingly, recent studies have reported that KDM4B-HOXC4-PD-L1 axis played an indispensable role in immune evasion of colorectal cancer cells (12). Therefore, the immune function of KDM4B in gynecological malignancies, especially in UCEC, has aroused great interest for us.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, extracellular vesicles overexpressing miR-15a inhibited the immune evasion of colorectal cancer cells via the KDM4B/HOXC4/PD-L1 axis. 24 Since PD-L1 is highly expressed in lung tumors 25 , 26 and we recently found differential expression of PD-L1 regulatory miRNAs in the serum of NSCLC patients, 14 we decided further to analyze their expression in the lung tumor tissues to ascertain whether these miRNAs have any clinical utility as prognostic and predictive biomarkers. To confirm the same, we correlated the expression patterns of the miRNAs mentioned above with survival outcomes, therapeutic response, and various clinicopathological parameters, including clinical stage and histology.…”
Section: Introductionmentioning
confidence: 99%
“…Exosome miR-424 from BMSCs could inhibit the malignant behavior of CRC cells by targeting TGFBR3 (102). Liu et al found that miR-15a derived from MSCs could inhibit the immune escape of CRC cells by modulating the KDM4B/HOXC4/ PD-L1 axis (103). In addition, Zhao et al also discovered that microRNA-34a-5p derived from tumorigenesis of CRC could be inhibited by MSC-derived extracellular vesicles through the c-MYC/ DNMT3a/PTEN axis (104).…”
Section: Roles Of Mesenchymal Stem Cells In Colorectal Cancermentioning
confidence: 99%